Does the distribution of the weekly training load account for the match results of elite professional soccer players? - Oliveira, R.; Brito, J. P.; Loureiro, N.; Padinha, V.; Ferreira, B.; Mendes, B. (Physiology & Behavior, 2020)
Purpose: The aim of the study was to compare training load (TL) of the days preceding a win, draw or defeat in a sample of elite professional soccer players across the in-season 2015/16. Methods: Twenty elite soccer players participated in this study. Total distance covered, high-speed running distance (HSRD), average speed, session rate of perceived exertion (s-RPE) and Hooper index scores (HI) were collected. Data from 24 weeks with one match were analysed through the match-day (MD-5, 4, 3, 2, 1) and MD+1. Results: The main finding emerges in MD-1, where a longer training duration preceding draws (95.1 ± 1.5 min) > defeats (91.5 ± 1.6 min) > wins (84.7 ± 0.5 min) was found, while total distance and average speed were higher in wins (3628.6 ± 57.2 m) > draws (3391.3 ± 153.3 m) > defeats (3236.1 ± 113.7 m) and draws (130.7 ± 17.6 m/min) > wins (86.0 ± 6.9 m/min) > defeats (54.8 ± 7.1 m/min), respectively. HSRD was higher in draws (42.8 ± 0.6 m) > wins (36.1 ± 1.7 m) > defeats (35.8 ± 1.7 m). In MD+1, there were differences in HI between wins vs draws (p<0.01). Conclusions: The results are drawn from one team that participated in UEFA Champions League. It was observed that different TL applied in training sessions can influence match result. Our findings can be considered in future soccer planning and periodization to win matches. This study emphasizes the use of HI especially in the day following the match.